2021
DOI: 10.1155/2021/5834915
|View full text |Cite
|
Sign up to set email alerts
|

Antiamylase, Antiglucosidase, and Antiglycation Properties of Millets and Sorghum from Sri Lanka

Abstract: The present study evaluated a range of biological activities of selected millet types and sorghum varieties in Sri Lanka in relation to diabetes and its complications management. Five millet types, namely, proso millet, white finger millet, kodo millet, foxtail millet, and finger millet (Oshadha and Rawana), and two sorghum varieties, namely, sweet sorghum and sorghum ICSV 112, were used in this study. Methanolic extracts of whole grains were studied for antiamylase, antiglucosidase, and early- and middle-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…It was also reported by Thornalley [ 24 ] that the evaluation of these compounds may reflect the glycation reaction process. Therefore, to prevent and manage the complications of diabetes, inhibitors which can reduce the glycation process are extremely valuable [ 25 ]. The effects of D. viscosa extract on the inhibition of dicarbonyl compounds are shown in Figure 2 B.…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported by Thornalley [ 24 ] that the evaluation of these compounds may reflect the glycation reaction process. Therefore, to prevent and manage the complications of diabetes, inhibitors which can reduce the glycation process are extremely valuable [ 25 ]. The effects of D. viscosa extract on the inhibition of dicarbonyl compounds are shown in Figure 2 B.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used method for assessing anti-glycation is the in vitro bovine serum albumin (BSA) glycation system [ 147 , 148 ]. This allows some of our common dietary products, such as yogurt, tea, and fruit, to exhibit some anti-glycation effect [ 149 , 150 , 151 , 152 , 153 ]. Obviously, these are not enough for people to experience significant anti-glycation effects.…”
Section: Discussionmentioning
confidence: 99%
“…turn exhibit antiaging effect. Senevirathne et al (2021) have very recently observed antidiabetic properties from different varieties of millets such as finger millet, proso millet, white finger millet, kodo millet, and foxtail millet cultivated in Sri Lanka. The inhibition of early glycation, middle glycation, and reversal of antiglycated products by these millets in diabetes make them crucial functional food for delaying the aging process.…”
Section: Bioactive Compounds: Antiaging and Antioxidant Propertiesmentioning
confidence: 99%